2019
DOI: 10.1136/bjsports-2018-100298
|View full text |Cite
|
Sign up to set email alerts
|

Return to play after surgery for isolated unstable syndesmotic ankle injuries (West Point grade IIB and III) in 110 male professional football players: a retrospective cohort study

Abstract: ObjectivesTo evaluate time to return to play following surgical stabilisation of isolated unstable syndesmosis injuries in a cohort of professional male football players.MethodsAll professional football players undergoing surgery for isolated unstable syndesmosis injury (West Point grade ≥IIB) at a specialised Orthopaedic and Sports Medicine Hospital were followed up until return to play (minimum ≥6 months). Players with a stable syndesmosis, injuries older than 6 weeks, concomitant medial or lateral malleolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 15 publications
0
65
1
2
Order By: Relevance
“…Although various authors have recommended arthroscopy [ 11 , 14 , 38 ], only one study mentioned chondral lesions detected by arthroscopy. Unfortunately, these were only reported as a side note, and neither their severity nor their treatment was documented [ 8 ]. Consequently, no study has yet in detail assessed the frequency of intra-articular pathologies in patients suffering an acute isolated, unstable syndesmotic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although various authors have recommended arthroscopy [ 11 , 14 , 38 ], only one study mentioned chondral lesions detected by arthroscopy. Unfortunately, these were only reported as a side note, and neither their severity nor their treatment was documented [ 8 ]. Consequently, no study has yet in detail assessed the frequency of intra-articular pathologies in patients suffering an acute isolated, unstable syndesmotic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, our clinical cohort consisted of a small amount of patients with syndesmotic lesions included, which might impair the generalizability of the findings. However, all patients were carefully selected after a detailed arthroscopic examination, which is currently considered as the gold standard in detecting syndesmotic ankle injuries (36,37). With regard to confirm the findings of our study, future research should therefore focus on the inclusion of more patients with high ankle sprains, as well as inclusion of healthy asymptomatic control patients from similar age groups.…”
Section: Discussionmentioning
confidence: 56%
“…Flexible devices were the preferred fixation construct (47.1%), followed by screws (29.6%), hybrid fixation (18%), and other (5.3%) (Figure 2). From our survey collection, we were able to infer that regardless of the severity of the injury to the syndesmosis, device choice and return to play protocol were not consistent internationally although the mean values of survey responses and those in D'Hooghe et al [13] were strikingly similar.…”
Section: Syndesmosis Injuries In Athletes: Return To Play and Rehabilmentioning
confidence: 81%
“…Similarly, there is no current consensus on a return to sport protocol for athletes to return to play following a syndesmotic injury. Data from a large study group [13] revealed that the mean time to begin on-field/sport-specific rehabilitation was 37 ± 12 days, with a mean time of 103 ± 28 days to the first match after syndesmotic stabilization [13].…”
Section: Discussionmentioning
confidence: 99%